Evolution of Science Education Foundations in Indonesia: Trends, Paradigms, and Future Directions - Novriandi; Efna Yulita; Iwit Sunarti; Tenti Putri Handayani; Hendrizal (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the evolution of science education foundations in Indonesia from 2021 to 2025 through a literature review approach. It aims to identify key trends, dominant paradigms, and contextual influences shaping the development of science teaching and learning in Indonesian formal education. The analysis reveals a significant shift from positivist to constructivist epistemologies, with increasing emphasis on inquiry-based learning, Nature of Science (NoS), and student-centered pedagogies. Curriculum reforms, particularly under the Merdeka Belajar policy, have introduced more flexible and learner-driven frameworks. However, disparities in implementation, teacher readiness, and resource availability persist across regions. Emerging trends also highlight the integration of local and indigenous knowledge into science instruction as a means to enhance relevance and inclusivity. The findings suggest that while theoretical advancements are evident, sustained efforts are needed to align policy, practice, and professional development. This review contributes to understanding how foundational shifts in science education can inform future curriculum design, teacher training, and educational policy in Indonesia.